Simulation research of improved internal model algorithm in temperature control of ceramic tooth sintering furnace - Wang, Yanchun; Li, Yanan; Liu, Chaoran; Guan, Changjun; Han, Guanghong (2022 IEEE International Conference on Artificial Intelligence and Computer Applications (ICAICA), 2022)
To improve the quality and efficiency of sintering of porcelain teeth, an improved control method for the internal mold is proposed. The control system is mainly used to precisely control the sintering temperature of porcelain teeth. The dynamic performance and steady-state performance of two closed-loop control schemes, the improved internal model controller (IIMC) based on the Gray Wolf optimization algorithm and the conventional PID controller, are compared. The results show that the improved internal model controller based on the optimized filtering time constant shortens the response time, improves the stability and anti-interference capability of the sintering furnace temperature control system, increases the temperature control accuracy, and thus improves the sintering quality of porcelain teeth.